Economies incentives, natural resources and conflict in Africa - Herbst, Jeffrey Ira (In:Journal of African economies;Oxford : Oxford Univ. Press, 1992;9(2000), 3, Seite 270-294;Online-Ressource, 2000)
This paper reviews how rebel leaders motivate followers to fight in wars in Sub-Saharan Africa. Almost all rebel leaders do use economic incentives, but they also avail themselves of other strategies to motivate their soldiers, including political indoctrination, ethnic mobilisation and coercion. The type of incentive employed will depend primarily on the nature of the state confronted. In particular, those movements that face competent national militaries will have to evolve into viable armies while rebels fighting states that are weak and corrupt can afford to lead movements that employ coercion and pursue economic agendas. (J Afr Econ/DÜI)
Keywords: Bürgerkrieg; Guerilla; Moral; Verband; Motivation; Militär; Führung; Einsatz; Bereitschaft